The current UP BLIS program and non-LAM information work a comparison of acquired and required skills and competencies - De Jesus, Annelle Fiona B.; Obille, Kathleen Lourdes B. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2019)
Today, there are new and emerging information professions in the Philippine job market, which are divergent from traditional library, Archives and Museum (LAM) work. This research determined the types of information work outside the LAM setting assumed by the graduates of the University of the Philippines Diliman School of Library and Information Studies (UPSLIS). This also identified discipline-specific and generic competencies required by such professions. This then assessed the current undergraduate program of UP SLIS against such required skills to gauge if the competencies necessary for non-LAM information work were adequately covered or taught in the UP Bachelor of LIS program. The study was facilitated through a semi-or structured survey that was administered via Google Forms. A total of twenty-two participants who belonged to UP SLIS classes of 2011 to 2018 were gathered for the research, with each batch having at least two representative participants.

Results of the study indicate that job titles most frequently assumed by the graduates are related to IT, networks and systems, web development, research, and administration. Among all LIS courses, ICT in LIS was deemed by the respondents as most relevant to their work. Likewise, ICT tracking was found by the graduates to be the specialization most useful for the performance of their tasks.

Findings of the research indicate that discipline-specific skills most required by the respondents’ work are IT (ICT skills, information & knowledge technologies e.g. database, search engines, digital repositories; systems design and developments social media and collaborative tools, open source systems); organizing knowledge and information (information architecture, database design and management); and knowledge, information and data management. Meanwhile, results show that generic skills most important for their work functions are time management, working with a team, working independently, strategic thinking and evaluation, and initiative.

Among the discipline-specific competencies, the following were shown to be greatly required but were not adequately covered by the current UP BLIS program: KM1 (knowledge management, information management, data management) and KM2 (knowledge synthesis/information integration, Knowledge transfer/organizational learning, organizational information /assets, knowledge sharing & collaboration). Among generic competencies, the following are greatly required but believed to have not been sufficiently acquired at UP SLIS: strategic thinking & evaluation communication, presentation, networking PR; interdisciplinary knowledge; understanding complex social, organizational and technical systems, time management, creativity, and economic reasoning.

The development of a new degree program specific to information science/management was recommended by the majority of the participants (91%). They also suggested including more practical and to accommodate core areas such as records management, multimedia archiving, data analytics, network & information systems administration, knowledge management and data management, risk management and graphic design or creation of marketing materials, as well as generic skills such as interpersonal skills, leadership, and management.
Thesis
Keywords: University of the Philippines -- School of Library and Information Studies; Library science -- Study and teaching -- Philippines; Curricula -- Evaluation -- Philippines